Study of causes and complications of intra uterine fetal death (IUFD) - Patel, Swapnil; Thaker, Rajal; Shah, Parul; Majumder, Siddhartha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Intra Uterine Fetal Death (IUFD) is tragic event for the parents and obstetrician. Identification of causes of IUFD will be helpful in counseling of parents as well as for formulating preventive measures. Objectives of current study were to study the causes of Intra Uterine Fetal Death (IUFD), associated complications and to suggest preventive measures. Methods: Study design: retrospective observational study. This study was carried out over a period of 3 months (April2014- June 2014) at a tertiary care hospital. Inclusion criteria was all IUFD >20 weeks of gestation. Results: Out of 1850 total births during the study period 80 IUFD occurred. Hence proportion of IUFD was 4.3%. In our study, Still Birth Rate (SBR) as per WHO criteria (28 weeks) was 22.1 per 1000. Registered patients were 24 (30%) whereas 56 (70%) were emergency admissions. Majority of cases, 48 (60%) were multigravidae with past obstetric history of abortion and IUFD in 13 (16.2%) and 9 (11.2%) respectively. In 31 (38.7%) no identifiable cause of IUFD was found whereas cause was identified in 49 (61.3%). IUFD occurred in 27 (33.7%) cases of PIH and eclampsia, out of them abruptio placenta was present in 10 (12.5%). Other causes of IUFD were anemia, oligoamnios, fever, congenital anomaly, cord accidents and jaundice in 9 (11.2%), 5 (6.2%), 3 (3.7%), 2 (2.5%), 2 (2.5%) and 1 (1.2%) respectively. Vaginal delivery occurred in 73 (91.2%) and 7 (8.7%) required surgical intervention. Most common complication associated with IUFD was Disseminated Intravascular Coagulation (DIC) in 18 (22.5%) followed by Sepsis in 8 (10%), Acute Renal Failure (ARF) in 3 (3.7%), Maternal mortality in 1 (1.2%). Conclusions: Anemia, PIH, accidental haemorrhage were leading causes of IUFD. Majority of women who had IUFD were emergency admission who had not received adequate antenatal care. A significant proportion of IUFD is preventable by health education to patients and community for regular antenatal care, about warning signs during antenatal period, hospital delivery and early referral.